Специфіка викладання теорії ймовірностей для студентів напряму «Соціологія» - Хомяк, Марія Ярославівна; Хомяк, Мария Ярославовна; Khomiak, Mariia Ia. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті зроблено спробу виявити основні труднощі викладання студентам напряму «Соціологія» курсу теорії ймовірностей та запропоновано шляхи їх подолання. Для того, щоб «донести» до студента основи теорії ймовірностей, виклад слід провадити не в класичній формі цієї науки, а мовою, доступною для соціологів; організувати курс таким чином, щоб основні положення теорії ймовірностей виростали з потреб соціології. An attempt to identify the main difficulties of teaching probability theory the students of direction «sociology» is done. They are: 1) in our schools students are not familiar with the concept of sampling and sample data (as opposite to the schools of Europe, the USA, etc.) while the introduction of the elements of theory of probability into the curricula is not effective; 2) a first-year student has not enough knowledge in sociology (including data processing); 3) most Ukrainian probability literature is intended for students of mathematical or economic occupations; 4) most probability provisions don’t have a direct application (if not to take into consideration mathematical statistics). Ways of overcoming them are suggested. So, a process of teaching should be provided in the language that is clear for a sociologist. Moreover, the main provisions of the probability theory should grow out of the needs of sociology.
The Specificity of Teaching of the Theory of Probability Students of Direction «Sociology»
Keywords: теорія ймовірностей; труднощі викладання; студент напряму «Соціологія»; probability theory; difficulties of teaching; a student of direction «sociology»